Effects of layer arrangement, pin size, polyurethane thickness, and polyurethane hardness on forming limits of Al/Cu bimetallic sheets through multi-point forming process - Milad Aali Majidabad; Ramin Hashemi; Habibolah Akbari (Journal of Materials Research and Technology)
This study experimentally evaluated the forming limit diagram (FLD) of Al/Cu bimetallic sheets fabricated using explosive welding in multi-point forming. The results showed that the forming limit was greater in multi-point forming than in the Nakazima test. It was also experimentally found that the forming limit was greater when copper was the lower layer in both multi-point forming and the Nakazima test. The experimental and theoretical results were in good agreement, with an error below 10%. Dimensional optimization was performed on the pin for multi-point forming, and the optimal pin size to maximize the forming limit was 12 mm in the presence and absence of the polyurethane layer. A rise in polyurethane hardness and thickness increased the forming limit, regardless of the pin size; however, the increase rate of the forming limit was falling at pin sizes of 10 and 12 mm and growing at pin sizes of 8 and 15 mm.